Relationships between immune parameters of saliva and blood - Mykola Petryshak; Ryta Seniv; Teodor Seniv; Walery Zukow (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
Background. The study of the relationships between the immune parameters of saliva and blood is of both theoretical and practical importance. The first is to study the relationships between systemic and local immunity, while the second is interesting as a non-invasive method of assessing the immune status and the influence of immunotropic drugs, including balneological, ecological etc. Material and Methods. The object of observation were 34 men and 10 women 24-70 y, who came to the Truskavets' spa for the treatment of chronic pyelonephritis combined with cholecystitis in remission. The testing was conducted twice, before and after balneotherapy for 7-10 days. Immune parameters of blood evaluated on a set of I and II levels recommended by the WHO. For phenotyping subpopulations of lymphocytes used the methods of rosette formation with sheep erythrocytes on which adsorbed monoclonal antibodies against receptors CD3, CD4, CD8, CD22 and CD56. Subpopulation of T cells with receptors high affinity determined by test of "active" rosette formation. The state of humoral immunity judged by the concentration in serum of Circulating Immune Complexes and Immunoglobulins classes M, G, A. Parameters of phagocytic function of neutrophils estimated in tests with cultures of Staphylococcus aureus and Escherichia coli. The set of immune parameters of saliva was IgG, IgA, secretory IgA and Lysozyme. Results. The correlations of the registered immune parameters of saliva as effective traits with the immune parameters of blood as factor traits were screened. The level of IgA in saliva, which is 88% (R=0,943) determined by immune parameters of blood, was found to be most closely related to them. Dependence on blood parameters of the level of secretory IgA was weaker, but still strong enough (R=0,801). Salivary IgG is associated with blood parameters to a similar extent (R=0,795), but the factor structure of the connection is significantly different from that of secretory IgA. The weakest were the connections of immune parameters of blood with the level of lysozyme in saliva (R=0,717). Conclusion. Saliva levels of IgG, both forms of IgA, and lysozyme are closely related to the immune parameters of the blood, so they can be markers of systemic immunity and its reactions to immunotropic effects.